Prevalence of smoking habits, attitudes and knowledge on counteractive strategies among a sample of healthcare employees: results of the smoking-free health environments project in the province of Palermo, Italy - Claudio Costantino; Claudio Costantino; Claudio Costantino; Claudio Costantino; Nicole Bonaccorso; Giuseppa Minutolo; Martina Sciortino; Giovanna Ripoli; Marco Berardi; Maurizio Gallo; Stefania Nastasi; Stefano Serra; et al. (Frontiers Media S.A., 2024)
IntroductionTobacco use is responsible for over 7 million deaths annually, making smoking the leading cause of preventable mortality globally. Over the last two decades in Italy, the prevalence of smoking among physicians has consistently decreased, while it remains higher and is gradually decreasing among non-physician healthcare workers. The aim of this study was to investigate the Prevalence of smoking habits, attitudes, and knowledge on counteractive strategies among employees in the Primary Healthcare Facilities in the Province of Palermo, Italy.MethodsA cross-sectional survey was conducted between June 2020 and December 2020 through a previously validated anonymous questionnaire structured in four sections including 34 items. Data were analyzed using Stata/MP 12.1 statistical software.ResultsOverall, 2,645 participants answered the questionnaire. The prevalence of either current or former smokers was 18.6%. Based on the multivariable analysis conducted, a significantly higher frequency of current smokers was observed among male participants (AdjOR: 1.29; CI95%: 1.02-1.64) and those belonging to the Surgical Unit (AdjOR: 1.92; CI95%: 1.27-2.90). Conversely, the prevalence of current smokers was significantly lower among those with at least one child (AdjOR: 0.67; CI95%: 0.49-0.91), with an educational qualification equal to or greater than a graduation degree (AdjOR: 0.56; CI95%: 0.43-0.73), those who considered second-hand smoke harmful (AdjOR: 0.06; CI95%: 0.008-0.60), those who had observed smoking or detected the smell of smoke in their workplace (AdjOR: 0.64; CI95%: 0.45-0.91). Furthermore, the prevalence of current smokers was significantly lower among participants who believed that healthcare professionals could play a crucial role in influencing their patients' lifestyles (AdjOR: 0.67; CI95%: 0.50-0.90) and among those who recommend their patients to quit smoking (AdjOR: 0.35; CI95%: 0.24-0.51).DiscussionThe results of the current research demonstrate that, despite the decline in smoking prevalence among physicians, the rate of smokers among healthcare facility employees remains unacceptably high. This underscores the need to re-evaluate current anti-tobacco strategies in the workplace.